PENGARUH STRUKTUR CORPORATE GOVERNANCE PADA KUALITAS LABA DENGAN INTELLECTUAL CAPITAL DISCLOSURE SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2010-2012) - Rusli Tohir; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2013)
This study aimed to examine the effect of corporate governance structure on earnings quality in the Indonesian banking companies. This study also examines whether the intellectual capital disclosure mediate the effect of corporate governance structure on earnings quality. The sample of this study was 24 banking companies listed in Indonesia Stock Exchange for the year 2010-2012. The collected data were processed using path analysis to examine the direct and indirect effect of corporate governance structure on earnings quality. Results of this study indicate that there is a direct effect of institutional ownership which is a component of corporate governance structure on earnings quality. Intellectual capital disclosure has no effect on earnings quality. Composition of independent directors and institutional ownership that is a component of corporate governance structure, effect on intellectual capital disclosure.